MEMBANGUN KARAKTER PROFETIK - Reky Lidyawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2017)
The problematic character in the life of society continues to experience increasingly complex developments, the advancement of science and technology has reformed the character probletics not only in the real world but also in cyberspace. This morality problematic must be overcome to realize the society that berakhlaqulkarimah. Strategies that can be done in tackling this problematic is to build a prophetic character. Character is related to character, character, psychological traits, character, personality or morals, then if we depart from human nature as a creature that can be educated, in fact the character can be directed and formed to be better than the previous. If there is someone who thinks that